Novel Synthetic oviductal fluid for Conventional Freezing 1 (SCF1) culture medium improves development and cryotolerance of in vitro produced Holstein embryos. (11th February 2022) - Owen, Corie M; Johnson, Melissa A; Rhodes-Long, Katherine A; Gumber, Diana J; Barceló-Fimbres, Moises; Altermatt, Joy L; Campos-Chillon, Lino Fernando
Abstract: In vitro produced (IVP) embryos hold great promise in the cattle industry; however, suboptimal in vitro culture conditions induce metabolic dysfunction, resulting in poor development and low cryotolerance of IVP embryos. This limits the use of IVP embryos in the cattle industry for embryo transfer and commercial scale-up. Previous studies have reported the use of individual metabolic regulators in culture media to improve blastocyst development rates and cryopreservation. In this study, we hypothesized that using a combination of select regulators, chosen for their unique synergistic potential, would alleviate metabolic dysfunction and improve the development of in vitro produced embryos to make them more closely resemble in vivo derived embryos. To test this, we first compared lipid content between Holstein and Jersey embryos produced in vivo and in vitro, and then systematically determined the combination of metabolic regulators that led to the greatest improvements in embryonic development, lipid content, mitochondrial polarity, and cryotolerance. We also tested different slow freezing techniques to further improve cryotolerance and finally validated our results via a clinical trial. Overall, we found that the use of multiple metabolic regulators in one culture media, which we refer to as Synthetic oviductal fluid for Conventional Freezing 1 (SCF1), and an optimized slow freezing technique resulted in improved pregnancy rates for frozen IVP embryos compared to embryos cultured in a synthetic oviductal fluid media. Additionally, there was no difference in pregnancy rate between frozen and fresh IVP embryos cultured in SCF1. This suggests that optimizing culture conditions and slow freezing technique can produce cryotolerance IVP and should allow further dissemination of this assisted reproductive technology. Lay Summary: In vitro produced (IVP) bovine embryos suffer from several physiological abnormalities that interfere with their ability to withstand the freezing process, a vital step in shipping and distribution of IVP embryos. To overcome these challenges, we performed a series of experiments to determine the optimal culture medium to best support the developing embryo. This new in vitro embryo culture medium is referred to as Synthetic oviductal fluid for Conventional Freezing 1 (SCF1). The medium is supplemented with various factors to more closely mimic the uterine environment, improve mitochondrial function, and decrease lipid accumulation. The results show that IVP embryos cultured in SCF1, slow frozen using an optimized technique, and transferred into recipients have a pregnancy rate that is similar to non-frozen IVP embryos. These findings suggest that SCF1 improves developmental competence of bovine IVP embryos and their ability to withstand cryopreservation, which can improve pregnancy rates and efficiency of assisted fertility operations within the dairy cattle industry. Abstract : This study shows that the use of a combination of metabolic regulators in in vitro bovine embryo production can enhance development and cryotolerance of embryos and result in higher pregnancy rates after transfer.